2016
DOI: 10.1177/1457496916659226
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarpal Injuries: Cone Beam Computed Tomography Arthrography, Magnetic Resonance Arthrography, and Arthroscopic Correlation among 21 Patients

Abstract: Cone beam computed tomography is an emerging imaging modality that offers several advantages over computed tomography and magnetic resonance imaging. Its usefulness particularly in ligamentous injuries should be further explored in a larger study. Cone beam computed tomography arthrography seems to offer similar sensitivity, specificity, and accuracy compared to magnetic resonance arthrography and therefore serves as a valuable option in evaluating patients with wrist pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
0
7
0
Order By: Relevance
“… 26 31 Two studies used cone-beam CT (CBCT) as index for diagnosing TFCC lesions. 37 42 In 12 studies, MRI was used as an index test. 23–25 27 30 32–35 37 40 41 The accuracy of MRI for TFCC, SLIL, LTIL and ulnotriquetral interosseous ligament (UTIL) lesions with high-resolution (3 T) techniques ranging from 89% to 91%, 75% to 92%, 91% and 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 31 Two studies used cone-beam CT (CBCT) as index for diagnosing TFCC lesions. 37 42 In 12 studies, MRI was used as an index test. 23–25 27 30 32–35 37 40 41 The accuracy of MRI for TFCC, SLIL, LTIL and ulnotriquetral interosseous ligament (UTIL) lesions with high-resolution (3 T) techniques ranging from 89% to 91%, 75% to 92%, 91% and 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the current review, five studies used another imaging tool, namely, radiograph, 36 US 26 31 and CBCT 37 42 for diagnosing non-chronic ligament and tendon injuries of the wrist. The diagnostic accuracy of radiograph was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT arthrograms 22 have been shown to have a slightly higher specificity than magnetic resonance arthrography. The sensitivity of CBCT arthrography is also better for cartilage lesions, except for those on the chondral surface of the lunate, according to Suojärvi et al 23 Suojärvi et al showed that 10/21 patients with wrist pain had cartilage injuries (47, 6%), indicating that cartilage injuries may be far more prevalent than previously documented. On regular radiographs, minor triquetral or ulnar-sided lunate sclerosis or cyst formation may be signs of ulnocarpal wear.…”
Section: Diagnosis and Evaluationmentioning
confidence: 94%
“…In contrast, palmar-flexed intercalated segment instability (PISI) is present with flexion of the lunate to palmar. This rather rare finding can be seen in midcarpal instability and lunotriquetral dissociation [17,28]. The acronyms "DISI" and "PISI" are descriptions for the pathological arrangement of the lunate in the central carpal column, but do not describe independent clinical conditions.…”
Section: Dissociative Carpal Instabilities (Cid)mentioning
confidence: 99%